Alcance de la subversión wittgensteiniana del cogito cartesiano - (:unkn) unknown (Universidad de Buenos Aires. Facultad de Filosofía y Letras. Instituto de Filosofía, 1999)
It is well known that Descartes' cogito is a turning point in philosophy and above all crucial controversial point; one with which almost every thinker since the XVII century has had to take a stand on. Even if Wittgenstein was not worried about the history of philosophy and the paid very little attention to its development, there are at least two aspects in his later philosophy that dispute the cogito, i.e. the so called private language argument and his conception of doubt and certainty. Both of these aspects are due to the importance given by Wittgenstein to ordinary public language. The purpose of this paper is to show how these two aspects combine in the debate against the cogito, and in so doing, to contrast the wittgensteinian criticism with the traditional anticogito claims. Within the wittgensteinian approach it is not only the cogito wich is aimed, but also the empiricist conception of meaning and the a priori representationism of the Tractatus.
63 ref.
Fil: Naishtat, Francisco. Universidad de Buenos Aires. Facultad de Filosofía y Letras; Argentina
Keywords: FILOSOFÍA; DESCARTES, RENÉ; CONCIENCIA; WITTGENSTEIN, LUDWING JOSEF JOHANN